Analisis Preferensi Konsumen Pada Jasa Kursus Bahasa Di Lembaga World English Pare - Mustaqim, Akhbar; Ayu N F A, Fatma; Mayasari, Andhika; Minto (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2025)
In the context of intense competition in the language education sector, it is essential for course providers to understand consumer preferences. This study focuses on World English Institution in Pare, which offers English language courses. The research aims to analyze consumer preferences regarding the language course services by considering five main attributes: teaching methods, class size, program types, price, and instructor qualifications. Using a quantitative approach, this study employs conjoint analysis to evaluate the utility values and importance of each attribute. The sample consists of 55 respondents aged 17 to 40 who are actively enrolled in courses at World English Institution. Findings indicate that teaching methods and instructor quality are the most influential factors in consumer preferences. Respondents favor interactive methods such as game-based learning and native-speaking instructors, as well as small class sizes that create a more personalized learning environment. The results provide strategic insights for course providers to improve service quality. By understanding consumer preferences, institutions can design programs better aligned with participants' needs, thereby enhancing student satisfaction and retention. This study is expected to serve as a reference for further research in the field of non-formal education. Dalam konteks persaingan yang ketat di sektor pendidikan bahasa, penting bagi lembaga kursus untuk memahami preferensi konsumen. Penelitian ini berfokus pada Lembaga World English di Pare, yang menawarkan kursus bahasa Inggris. Penelitian ini bertujuan untuk menganalisis preferensi konsumen terhadap layanan kursus bahasa dengan mempertimbangkan lima atribut utama: metode pengajaran, ukuran kelas, jenis program, harga, dan kualifikasi pengajar. Menggunakan pendekatan kuantitatif, penelitian ini menerapkan analisis konjoin untuk mengevaluasi nilai utilitas dan kepentingan setiap atribut. Sampel terdiri dari 55 responden berusia 17 hingga 40 tahun yang aktif mengikuti kursus di Lembaga World English. Temuan menunjukkan bahwa metode pengajaran dan kualitas pengajar adalah faktor paling berpengaruh dalam preferensi konsumen. Responden lebih menyukai metode interaktif seperti game learning dan pengajar yang merupakan native speaker, serta ukuran kelas kecil untuk suasana belajar yang lebih personal. Hasil penelitian ini memberikan wawasan strategis bagi lembaga kursus untuk meningkatkan kualitas layanan. Dengan memahami preferensi konsumen, lembaga dapat merancang program yang lebih sesuai dengan kebutuhan peserta, sehingga meningkatkan kepuasan dan retensi siswa. Penelitian ini diharapkan menjadi referensi untuk studi lebih lanjut di bidang pendidikan nonformal.